A discourse analysis of the 2009 Bangladesh education policy in the local media / Mohsina Akter - Akter, Mohsina (2014)
The National Education Policy 2009 is one of the most important issues in the advancement of the education system in Bangladesh. This policy is also the latest in a series of education policies since the independence in 1971. The policy was initiated in April 9, 2009 and work on this education policy was completed on September 2, 2009. During finalizing the policy a lot of opinions were published in the newspapers in the form of editorials. The editors turned to the newspapers to give their opinions about the policy. The study analyses the editorial discourses on the Bangladesh education policy 2009 to look at the processes in the texts to understand the predominant events and judgements towards the policy. The study uses Halliday’s ideational and interpersonal metafunctions to analyse the editorials. The ideational metafunction is used to uncover the processes of texts of editorials to understand the predominant events. The interpersonal metafunction of the editorials has been done to explore the attitudes and judgments of the editorial writers. The resources of appraisal have been used to express the attitude and engagement of the editorial writers about the education policy. The analysis is centered on twenty editorials from selected newspapers (The Daily Star, The Independent, New Age, e-Bangladesh, and The Financial Express). The methods of analysis used to analyse the selected opinion editorials are the Systemic Functional Grammar (SFG) including the resources of Appraisal based on Halliday’s discourse properties (Halliday and Matthiessen, 2004). Halliday’s Systemic Functional Grammar (SFG) has been used to disclose how the grammar functions to generate an experience of the world and present the writer’s point of view. In addition, contextual analysis has been carried out together with the linguistic features to show the process in a text and to realize the principal events or relationships. Finally, a systematic analysis of editorials has been performed to show the ideational and interpersonal meaning using the resources of appraisal available in editorials.